GAMBARAN SIMTOM KECEMASAN PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA DI RUMAH SAKIT KHUSUS GINJAL RASYIDA - RANGGA PRADIDO; SHAHRUL RAHMAN (JURNAL ILMIAH SIMANTEK, 2021)
Anxiety is a disorder that is triggered by the existence of a a clear situation or object (from outside the individual itself), whichactually does no harm. Unresolved anxiety can lead to some impact on which a person tends to have a negative assessmentof the meaning of life, decreased quality of life, emotional changes such as chronic depression and psychosis disorders.The general objective in this research is to find out the symptoms of anxiety symptoms of chronic kidney disease patientsundergo hemodialysis. This research is a descriptive study with cross sectional design, This study uses a sampling methodthat is non-probability sampling type quota sampling. Calculated using the Slovin formula: and obtained a sample amount of171. The proportion of patient with chronic kidney disease treated with hemodialysis in Rasyida, kidney speciality hospitalbased on the anxiety level resulting mild anxiety (86,5%) and moderate anxiety (13,5%). There are symptoms of anxietysymptoms in patients with chronic kidney disease undergoing hemodialysis.